Impaired flow-mediated vasodilatation is associated with increased left ventricular mass in a multi-ethnic population. The Northern Manhattan Study - Hasegawa, Takuya (2010)
BACKGROUND: Increased left ventricular (LV) mass and endothelial dysfunction are important risk factors for cardiovascular mortality and morbidity. However, it is not clear whether endothelial dysfunction is associated with increased LV mass. We tested the hypothesis that impaired flow-mediated vasodilatation (FMD) is associated with increased LV mass in a population-based multi-ethnic cohort. METHODS: As a part of the Northern Manhattan Study, we performed two-dimensional echocardiography and FMD assessment during reactive hyperemia by high-resolution ultrasonography in 867 stroke-free community participants. LV mass was calculated according to an established method. LV hypertrophy was defined as the 90th percentile of sex-specific LV mass indexed for body surface area among normal subjects. Multivariable models were used to test the association of FMD with LV mass. RESULTS: In multiple linear regression analyses adjusting for age, sex, body mass index, systolic blood pressure, antihypertensive medications, low-density lipoprotein cholesterol, diabetes, smoking, hematocrit, and race-ethnicity, FMD was inversely associated with LV mass (β = −1.21 ± 0.56, P = 0.03). The association persisted after further adjustment for any component of blood pressure (systolic, mean, and pulse pressure). In univariate logistic regression analysis, each 1% decrease in FMD was associated with a 8% higher risk of LV hypertrophy [odds ratio (OR) 1.08, 95% confidence interval (CI) 1.03–1.13 per each FMD point P< 0.01]. CONCLUSIONS: Impaired FMD is associated with LV mass, independent of other factors associated with increased LV mass. Endothelial dysfunction might be a potential risk factor for LV hypertrophy.